2019
DOI: 10.3389/fcimb.2019.00414
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Gallium as an Antifungal Agent

Abstract: There are only few drugs available to treat fungal infections, and the lack of new antifungals, along with the emergence of drug-resistant strains, results in millions of deaths/year. An unconventional approach to fight microbial infection is to exploit nutritional vulnerabilities of microorganism metabolism. The metal gallium can disrupt iron metabolism in bacteria and cancer cells, but it has not been tested against fungal pathogens such as Aspergillus and Candida. Here, we investigate in vitro activity of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 36 publications
1
50
0
1
Order By: Relevance
“…A link between iron chelation and caspofungin susceptibility has also been observed (59,60). Gallium is a metal compound that can be taken up by cellular iron transport systems, replacing it in iron-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between iron chelation and caspofungin susceptibility has also been observed (59,60). Gallium is a metal compound that can be taken up by cellular iron transport systems, replacing it in iron-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Gallium is a metal compound that can be taken up by cellular iron transport systems, replacing it in iron-containing proteins. However, it cannot be reduced under physiological conditions, inhibiting the functionality of gallium-complexed proteins and arresting growth (59). We demonstrated previously that gallium nitrate III [Ga(NO 3 ) 3 ] has a synergistic effect with caspofungin but not with azoles and that it impairs CPE (59).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Goldman et al evaluated the potential of gallium, already known for its antibacterial activity, as antifungal [ 157 ]. They demonstrated that gallium nitrate had a fungistatic action against fungi.…”
Section: Metal Metal Complexes and Metalloidsmentioning
confidence: 99%
“… * Antifungal susceptibility testing was interpreted according to the document M27-S3 published by CLSI; n , number of fungal isolates; the references used to construct this table were [ 5 , 7 , 25 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. …”
Section: Figurementioning
confidence: 99%
“… a CAS, caspofungin; MCF, micafungin; ANF, anidulafungin; b MIC 50 , MIC at which 50% of isolates were inhibited; c MIC 90 , MIC at which 90% of isolates were inhibited; Modal MICs are indicated with underlined numbers; MIC values of <0.03 were allocated as ≤0.015; Clinical and Laboratory Standards Institute (CLSI) document M27S3 suggests the following breakpoints for echinocandins against Candida spp. : susceptible ≤ 2 mg/L and non-susceptible > 2 mg/L; the references used to construct this table were [ 5 , 29 , 31 , 34 , 35 , 38 , 39 , 40 , 41 , 42 , 44 , 46 , 47 ]. …”
Section: Figurementioning
confidence: 99%